2018
DOI: 10.1002/icd.2088
|View full text |Cite
|
Sign up to set email alerts
|

Family stress predicts poorer dietary quality in children: Examining the role of the parent–child relationship

Abstract: The present prospective study investigated a comprehensive model of family stress to explain changes in young children's diet quality from age 3 to 5 years. The direct associations of family stress with child diet quality were examined, as well as the indirect associations via features of the parent-child relationship, including inconsistent parenting practices, negative parent-child interactions, and poor emotional bond. Using an Australian sample of 579 mother-child dyads (child M age = 3.05 years; 45% boys)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
0
18
2
Order By: Relevance
“…In 10 studies, researchers examined the relationship between parents' life event stressors and children's weight and health behaviors . Stress from financial strain within a family was positively associated with children's weight status .…”
Section: Resultsmentioning
confidence: 99%
“…In 10 studies, researchers examined the relationship between parents' life event stressors and children's weight and health behaviors . Stress from financial strain within a family was positively associated with children's weight status .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the extended UNICEF care model of child nutrition and obesity suggests that socio-emotional adversity, such as elevated maternal depression and stress, and reduced educational and economic resources, are associated with poorer child diet quality because adversity interferes with parental functioning and parent-child relationship quality (El-Behadli et al, 2015). This was supported by a recent study which found family stress at child age 3 years (indicated by maternal psychological distress, poor health, exposure to stressful events, and financial hardship) to be predictive of poorer child diet quality at age 5 years, and this pathway was partially indirect via impaired parent-child relationship quality (Webb et al, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…In a study of “irregular eating habits” during early childhood, children of mothers who reported having fair/poor health around childbirth, compared to mothers in excellent health, showed increased odds of eating irregularity between ages 2 and 4 years (McDermott et al, ). Finally, one study was found (Webb et al, ) which independently examined maternal health as a correlate of child diet quality, with results showing that poorer maternal health at child age 3 years was correlated with lower child intake of fruit and vegetables, and higher intake of sugar, both concurrently and 2 years later at child age 5 years. Given the importance of both physical and psychological health for optimal functioning (Witmer & Sweeney, ), the present study also evaluates maternal self‐rated health as a predictor of breastfeeding duration and child feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rani, & Barber, 2018), as well as disturbing sleep and affecting physical pain and illness (see earlier sections). Studies integrating tests of the role of peer victimization in physical health as mediated by social and emotional adjustment are quite important directions for the future.…”
mentioning
confidence: 99%